JURIDICAL ANALYSIS OF THE ROLE OF IMMIGRATION IN PREVENTING THE CRIME OF TRAFFICKING IN PERSONS (RESEARCH STUDY AT THE SPECIAL CLASS I IMMIGRATION OFFICE OF TPI BATAM) - Muhammad Aris Fitrah Nasution; Siti Nurkhotijah; Darwis Anatami (CV. RADJA PUBLIKA, 2025)
The crime of trafficking in persons (TPPO) is a form of transnational crime that continues to grow and threatens human rights, especially in border areas such as Batam, which is one of the strategic routes to neighboring countries. The Immigration Office, as a law enforcement institution in the field of immigration, has a vital role in preventing the practice of trafficking through its supervisory functions and administrative actions at the entrances and exits of Indonesian territory. This study aims to analyze legal arrangements and implementation, as well as obstacles and solutions to immigration's role in preventing trafficking, with a focus on the Special Class I Immigration Office of TPI Batam. This study uses normative and empirical juridical methods, with a statute approach and a socio-legal approach. Data was collected through literature studies, observations, and interviews with Immigration officials and officers. The theories used in the analysis include the Theory of the State of Law, the Theory of the Legal System, and the Theory of Legal Certainty. The results of the study show that national and international legal arrangements have provided an adequate basis for the role of Immigration in the prevention of trafficking. However, its implementation in the field still faces a number of obstacles, including limited administrative authority, a lack of data integration between agencies, limited human resources, and a lack of optimal understanding of trafficking indicators. For this reason, it is necessary to update more technical SOPs, increase cross-sector and international cooperation, provide continuous training for officers, and strengthen information systems and surveillance technology as an integrated solution strategy.